2014
DOI: 10.1016/j.hjdsi.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

EHR adopters vs. non-adopters: Impacts of, barriers to, and federal initiatives for EHR adoption

Abstract: While adoption of electronic health record (EHR) systems has grown rapidly, little is known about physicians’ perspectives on its adoption and use. Nationally representative survey data from 2011 are used to compare the perspectives of physicians who have adopted EHRs with those that have yet to do so across three key areas: the impact of EHRs on clinical care, practice efficiency and operations; barriers to EHR adoption; and factors that influence physicians to adopt EHRs. Despite significant differences in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 15 publications
(20 reference statements)
2
40
0
Order By: Relevance
“…Moreover, ambulatory care in the German language region is increasingly characterized by the formation of medical networks that goes along with a higher demand for information exchange among healthcare Previous studies in this field suggested that health IT adoption is also associated with age and sex [5,14,16,29,[49][50][51]. Our results suggest that young age (30−39 years) and male sex are predictors of EHR adoption but have only limited impact on the adoption of the surveyed electronic workflows supporting health data exchange.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Moreover, ambulatory care in the German language region is increasingly characterized by the formation of medical networks that goes along with a higher demand for information exchange among healthcare Previous studies in this field suggested that health IT adoption is also associated with age and sex [5,14,16,29,[49][50][51]. Our results suggest that young age (30−39 years) and male sex are predictors of EHR adoption but have only limited impact on the adoption of the surveyed electronic workflows supporting health data exchange.…”
Section: Discussionmentioning
confidence: 60%
“…Another objective of our study was to investigate the effect of physicians' attitude towards health IT on health IT adoption, use of electronic workflow practices and the intention to expand individual health IT use in the future, because a lot of qualitative studies suggested that there exists an association [5,14,16,29,[31][32][33][34][35][36]. Indeed, it emerged that physicians' attitude towards health IT was an independent predictor on most outcomes (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 We need to continue to track and understand the factors holding nonadopters back so that the next generation of policies can be designed to result in universal use of EHR systems.…”
Section: Policy Implicationsmentioning
confidence: 99%